INFLUENCE MARKETING MIX AND SERVICE QUALITY ON CONSUMER PURCHASING DECISIONS AT CORNER CELL - Prasasti, Heni Eka; Raharjo, Itot Bian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The aim of this research is to determine the influence of marketing mix and service quality on consumer purchasing decisions at corner cells Design/Methode/Approach : This research uses a descriptive quantitative approach method. The population in this research is all corner cell consumers whose number is unlimited. The sample used in this research was 60 respondents taken using random sampling techniques. Data collection techniques use questionnaires. Data analysis in this research uses the multiple linear regression method. Research Finding : This research found that marketing mix and service quality have an influence on consumer purchasing decisions by 81.6% compared to other factors. Theoretical contribution/Originality : This research provides a theoretical contribution by integrating the concepts of marketing mix and service quality in the context of the mobile retail industry. In previous literature, marketing mix and service quality are often studied separately. However, this research shows that the combination of these two elements has a significant influence on consumer satisfaction. Thus, this research adds to the understanding of how optimal marketing and service strategies can be implemented simultaneously to improve consumer purchasing experience and satisfaction Practitionel/Policy implication : The results of this research provide practical guidance for Corner Cell management in designing more effective marketing and service strategies. By understanding that the combination of a good marketing mix and high service quality significantly increases customer satisfaction, management can focus resources on optimizing these aspects. For example, increasing staff training to improve service quality or adjusting promotional strategies to better attract customers. At the policy level, these results can be used to develop policies that support more holistic and customer-focused marketing practices. Research limitation : This research is limited to a sample of corner cell consumers located in Banggi Village, Kediri City, so the results may not be generalized to all retail stores.